Non-contacted intelligent access control system based on EAIDK310 and OneNET cloud platform - Lou Chenzhe; Xia Kun; Zhang Wenjun; Mo Yingdong (Dianzi Jishu Yingyong)
In the era of Internet of Things, smart home, as an important part of people′s daily life, is developing rapidly. This paper designs a contactless intelligent access control system based on EAIDK310 and OneNET cloud platform, using the EAIDK310 AI development kit jointly developed by Arm and Open AI Lab as the system control core, and realizing contactless access control through face recognition, gesture recognition, voice interaction and other functions within the main control board. This work uses the more mature convolutional neural network in artificial intelligence and the leading edge of Baidu AI open platform for face recognition, gesture recognition and voice interaction in real time, which can maintain a very high recognition accuracy while ensuring a fast enough recognition speed, and the introduction of live detection to avoid unscrupulous elements using photos to cheat the system, making the whole access control system more secure. This work uploads data to the mobile OneNET cloud platform through Wi-Fi, and interacts with WeChat applet for data images, so that the owner can unlock the access control system and other operations through his cell phone at any location, and can monitor real-time images outside the access control, which can provide protection in terms of occupant security.